Solvent-directed synthesis of two Cu(II)-based coordination polymers: structural diversity and protective effect on viral myocarditis by reducing inflammatory response in myocardial cells. Issue 12 (1st December 2020) - Yu, Li-Jun; Bai, Dong-Song; Tang, Wen-Li; Bi, Fu-Long; Liu, Si-Jun
Abstract: Two Cu(II)-based coordination polymers with the chemical formula of [Cu(bibb)(1, 4-NDC)](DMF) (1, bibb = 1, 4-bis(benzimidazol-1-yl)−2-butylene, 1, 4-H2 NDC = 1, 4-naphthalenedicarboxylic acid, DMF = N, N-dimethylformamide) and [Cu(bibb)(1, 4-NDC)](DMA) (2, N, N-dimethylacetamide) have been prepared. The structural solution and refinement results based on the crystal data show that complex 1 exhibits a rarely 2-fold interpenetrating 3D (4, 5)-connected xah framework, and complex 2 possesses an unusual 3D (3, 4)-connected dmc topology. Furthermore, the protective activity of compounds 1 and 2 on Viral myocarditis (VMC) was detected on CVB3-induced mouse viral myocarditis model. The relative expression of the inflammatory factors nf-κb and p38 in myocardial cells after compounds 1 and 2 treatment was measured with reverse transcription-polymerase chain reaction (RT-PCR). The release level of the inflammatory cytokines IL-1 and MCP-1 by myocardial cells was determined with enzyme linked immunosorbent assay (ELISA) detection kit.